Parenting in Plastic Surgery Residency. Issue 6 (18th April 2022) - Wallace, Chelsea C.; Edmunds, R. Wesley; Bourne, Debra; Wong, Lesley
Abstract : Background: In 1994, Mackinnon advocated that plastic surgery residents should have accessible child care to promote a productive return to work. Decades later, lack of adequate child care remains a dilemma for trainees. The authors' survey aims to evaluate childrearing during plastic surgery training. Methods: An anonymous, voluntary survey was sent to plastic surgery residents. It evaluated demographics, childcare accommodations, and attitudes/issues surrounding childrearing during residency. Results: There were 32 respondents: 66 percent women and 34 percent men. Seventy-five percent were married, and 38 percent were parents. Seventy-five percent of male parents compared to 12 percent of female parents reported that their spouse was the primary childcare source. One hundred percent of respondents with children reported that child care creates a financial burden. Three percent of respondents felt their institution provided services to arrange adequate child care. Sixty-three percent of residents felt their program did not allow flexibility to accommodate childcare needs. Female residents missed work twice as often and were twice as likely to require a co-resident to cover clinical duties because of childcare difficulties when compared to male residents ( p = 0.296 and p = 0.145). Sixty-seven percent of women agreed with the statement, "If you had to pick a residency program today, the availability of on-site child care would influence your decision, " compared to only 9 percent of men ( p = 0.002). Conclusions: Training institutions are not meeting the childcare needs of plastic surgery trainees. If the specialty wishes to recruit and retain the top applicants, it must improve the childcare accommodations for residents. All institutions with plastic surgery residency programs should provide affordable, accessible child care that accommodates the 24-hour natures of both patient care and parenthood.